2019
DOI: 10.1002/jcp.29329
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0080425 inhibits cell proliferation and fibrosis in diabetic nephropathy via sponging miR‐24‐3p and targeting fibroblast growth factor 11

Abstract: Diabetic nephropathy (DN) is a severe end-stage kidney disease developed from diabetes mellitus. The involvement of circular RNAs (circRNAs) in modulating DN pathogenesis has been implied, but underlying mechanism is still lacking. In this study, we demonstrated that the expression of circ_0080425 correlated with the DN progression, and exerted positive effect on cell proliferation and fibrosis in mesangial cells. Further assessment suggested that circ_0080425 function as sponge harboring miR-24-3p. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…Moreover, miR-24-3p can be regulated by several lncRNAs in numerous types of cancer, including hepatocellular carcinoma (34), prostate cancer (35) and lung cancer (36). miR-24-3p is also sponged by circ_0080425 in diabetic nephropathy, leading to cell proliferation and fibrosis inhibition (37). However, the sponge regulation of miR-24-3p by circRNAs in NSCLC remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-24-3p can be regulated by several lncRNAs in numerous types of cancer, including hepatocellular carcinoma (34), prostate cancer (35) and lung cancer (36). miR-24-3p is also sponged by circ_0080425 in diabetic nephropathy, leading to cell proliferation and fibrosis inhibition (37). However, the sponge regulation of miR-24-3p by circRNAs in NSCLC remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…in gastric cancer, the knockdown of hsa_circ_0001368 results in accelerated tumor growth in vivo and may act as a cerna to sponge mir-6506-5p and play a tumor-suppressive role (28). liu et al (29) suggested that circ_0080425 functions as sponge, harboring mir-24-3p, which inhibits cell proliferation and fibrosis in dn by targeting fibroblast growth factor 11. Furthermore, Yao et al (30) demonstrated that circ_0000285 aggravates podocyte injury through sponging mir-654-3p and activating MaPK6 in dn.…”
Section: Discussionmentioning
confidence: 99%
“…circRNA hsa_circ_0054633 was found to be elevated in pre‐diabetes and type 2 diabetes patients' peripheral blood and might serve as a diagnostic biomarker, which provides new ideas for the diagnosis of type 2 diabetes 17 . Some circRNAs have a potential role in diabetic retinopathy, 18,19 diabetic nephropathy, 20 diabetes‐related coronary artery disease, 21 diabetes‐related depression 22 and gestational diabetes mellitus 23 . However, the roles of circRNAs in T1D mellitus are largely unknown.…”
Section: Introductionmentioning
confidence: 99%